Peripartum management of hypertension: a position paper of the ESC Council on Hypertension and the European Society of Hypertension. Issue 6 (16th December 2019) - Cífková, Renata; Johnson, Mark R; Kahan, Thomas; Brguljan, Jana; Williams, Bryan; Coca, Antonio; Manolis, Athanasios; Thomopoulos, Costas; Borghi, Claudio; Tsioufis, Costas; Parati, Gianfranco; Sudano, Isabella; et al.
Abstract: Hypertensive disorders are the most common medical complications in the peripartum period associated with a substantial increase in morbidity and mortality. Hypertension in the peripartum period may be due to the continuation of pre-existing or gestational hypertension, de novo development of pre-eclampsia or it may be also induced by some drugs used for analgesia or suppression of postpartum haemorrhage. Women with severe hypertension and hypertensive emergencies are at high risk of life-threatening complications, therefore, despite the lack of evidence-based data, based on expert opinion, antihypertensive treatment is recommended. Labetalol intravenously and methyldopa orally are then the two most frequently used drugs. Short-acting oral nifedipine is suggested to be used only if other drugs or iv access are not available. Induction of labour is associated with improved maternal outcome and should be advised for women with gestational hypertension or mild pre-eclampsia at 37 weeks' gestation. This position paper provides the first interdisciplinary approach to the management of hypertension in the peripartum period based on the best available evidence and expert consensus.